Answer:
S = 13 - x
T = (18 + x) / 2
Step-by-step explanation:
S = 18
T= 18
Sue gives away x, so subtract it from 18. But Tony gets x, so add it to 18 in his expression.
S = 18 - x
T= 18 + x
Sue eats 5 so subtract 5 from her expression. Tony eats half, so divide his expression by 2.
S = 18 - x - 5
T = 18 + x / 2
Simplify 18-5.
S = 13 - x
T = (18 + x) / 2
Answer:
3x^2y
Step-by-step explanation:
Find the cubic root of each term
The first one is a reflection over the x-axis :)
I'm not sure what this means. If you have choices you should list them.
(1/2)*(1/4 + 1/6) is an example of what should be given. There are two ways to solve this.
1. Use the distributive property.
1/2*1/4 + 1/2* 1/6
1/8 + 1/12 Which can be added using the LCD of 24
3/24 + 2/24 = 5/24
Method 2
Add what is inside the brackets first.
1/2 ( 1/4 + 1/6)
1/2(3/12 + 2/12 = 5/12
Now multiply by 1/2
1/2(5/12) = 5*1/(12 * 2) = 5 / 24 Same answer.